2019
DOI: 10.1002/aoc.4863
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse CuPt alloy nanoparticles assembled on reduced graphene oxide as catalysts in the transfer hydrogenation of various functional organic groups

Abstract: We present herein a new nanocatalyst, namely binary CuPt alloy nanoparticles (NPs) supported on reduced graphene oxide (CuPt‐rGO), as a highly active heterogeneous catalyst for the transfer hydrogenation (TH) protocol that is demonstrated to be applicable over the reduction of various unsaturated organic compounds (olefins, aldehydes/ketones and nitroarenes) in aqueous solutions at room temperature. CuPt alloy NPs were synthesized by the co‐reduction of metal (II) acetylacetonates by borane‐tert‐butylamine (BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As such, the mechanisms of both reactions may be similar. Hydrogenation of 4‐nitroaniline using boranes generally follow either a tandem reduction pathway, [65–70] or a transfer hydrogenation pathway [62,71–73] . A tandem hydrogenation first produces hydrogen, which is then used as reductant in an ensuing reaction [38,66,74] .…”
Section: Resultsmentioning
confidence: 99%
“…As such, the mechanisms of both reactions may be similar. Hydrogenation of 4‐nitroaniline using boranes generally follow either a tandem reduction pathway, [65–70] or a transfer hydrogenation pathway [62,71–73] . A tandem hydrogenation first produces hydrogen, which is then used as reductant in an ensuing reaction [38,66,74] .…”
Section: Resultsmentioning
confidence: 99%
“…Based on our earlier attempts at hydrogenation and reductive amination, [20][21][22][23][24][25] we tried to optimize the hydrogenation conditions by experimenting with different parameters, such as solvent, temperature, time, the catalyst, and the amount of AB. 4′-Methoxyacetophenone was selected as the model reagent for the synthesis of the corresponding alcohol under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] In our previous studies, we have presented some protocols using AB as a hydrogen source with reduced graphene oxide-supported bimetallic NiPd alloy nanoparticles (NPs), 20 graphene hydrogel-supported Pd NPs, 21 and CuPt alloy NPs assembled on reduced graphene oxide as a catalyst, respectively. 22 In a recent study, we have also demonstrated that in situ synthesized Pd NPs supported on mesoporous graphitic carbon nitride (mpg-C 3 N 4 /Pd) are highly efficient catalysts in the A facile and highly efficient transfer hydrogenation of ketones and aldehydes catalyzed by palladium nanoparticles supported on mesoporous graphitic carbon nitride TH of nitroarenes to the corresponding aniline derivatives at room temperature. 23 In order to clarify the efficiency of the newly developed mpg-C 3 N 4 /Pd catalyst, we describe herein an efficient, selective, and fast reduction chemistry method for the synthesis of alcohols using AB as a hydrogen source with mpg-C 3 N 4 /Pd in a water/methanol mixture (v/v = 1/1).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation